2022
DOI: 10.2118/212284-pa
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Model to Predict Production Rate of Electrical Submersible Pump Wells

Abstract: Summary Production data are essential for designing and operating electrical submersible pump (ESP) systems. This study aims to develop artificial neural network (ANN) models to predict flow rates of ESP artificially lifted wells. The ANN models were developed using 31,652 data points randomly split into 80% (25,744 data points) for training and 20% (5,625 data points) for testing. Each data set included measurements for wellhead parameters, fluid properties, ESP downhole sensor measurements, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This leads to another challenge in developing data-driven models, which is the lack of transparency and interpretability of some algorithms. From the data-driven applications studied in the literature, , we have concluded that their workflow starts with the usage of more complex black-box algorithms without applying more interpretable machine learning algorithms. Therefore, the proposed methodology comprises three modeling steps: symbolic regression, XGBoosting, and deep learning.…”
Section: Literature Studymentioning
confidence: 99%
“…This leads to another challenge in developing data-driven models, which is the lack of transparency and interpretability of some algorithms. From the data-driven applications studied in the literature, , we have concluded that their workflow starts with the usage of more complex black-box algorithms without applying more interpretable machine learning algorithms. Therefore, the proposed methodology comprises three modeling steps: symbolic regression, XGBoosting, and deep learning.…”
Section: Literature Studymentioning
confidence: 99%